Association of obesity with reproductive hormones alterations, DNA fragmentation and protamine deficiency in human spermatozoa - Maged M. Yassin; Saleh N. Mwafy; Mohammed M. Laqqan (Middle East Fertility Society Journal)
Abstract Background Obesity is a major public health concern worldwide, causing negative impacts on reproductive function due to metabolic and physiological abnormalities. The incidence of obesity has paralleled the incidence of male infertility. This study was conducted to evaluate alterations in male reproductive hormones, DNA fragmentation levels, and protamine deficiency in human spermatozoa, and to examine their association with body mass index (BMI). This case–control study included 450 males with an average age of 34.3 ± 8.0 years. The male participants were divided into two groups based on their BMI status: (I) normal-weight males with at least two children (n = 200) and (II) obese males (n = 250). After three days of abstinence, semen samples were collected from all participants and analyzed. Peripheral blood was also obtained on the same day for hormonal analysis. Sperm DNA fragmentation and protamine deficiency were assessed using the TUNEL assay and chromomycin A3 staining, respectively. Results Significant declines were found in semen volume, sperm count, percentage of total sperm motility, and progressive motility in obese males compared to normal-weight males (P < 0.001). Conversely, there were significant increases in the percentage of sperm with non-progressive motility, non-motile spermatozoa, and sperm with an abnormal form in obese males (P < 0.001). Additionally, obese males have significantly higher levels of spermatozoa DNA fragmentation, protamine deficiency, and elevation in PRL level than normal-weight males (P < 0.001). On the other hand, the levels of testosterone, LH, and FSH were lower in obese males (P < 0.001). Conclusion Obesity adversely affects male fertility by altering semen parameters, reproductive hormones, the level of sperm DNA fragmentation, and protamine deficiency.